An analytical solution to temperature field distribution in a thick rod subjected to periodic-motion heat sources and application in ball screws. Issue 12 (2nd December 2021) - Sheng, Xin; Lu, Xi; Zhang, Jianrun; Lu, Yunqiao
ABSTRACT: In this work, an analytical solution to temperature field distribution in a finite cylinder body caused by constant-strength, periodic-motion heat sources is obtained. Two heat source models, i.e. single and multiple, are proposed. The analytical solution is applied in calculating the temperature rise of a Z -direction feeding ball screw. The plotted temperature rise curves show that the error of the two models is 0.5% and they are both reasonable for theoretical calculation as they show the same trend as a test value curve. The maximum error of surplus temperature in the steady state between the calculated values and test results of the single heat source model is 14.1%, which is acceptable in engineering applications.